Wide speed range operation of permanent magnet vernier machines. Issue 18 (1st September 2018) - Arif, A.; Baloch, N.; Kwon, B.I.
Abstract : This letter proposes winding switching for the high‐performance of permanent‐magnet vernier machines (PMVMs) in wide speed range operation. The machine is operated in two modes: cumulative and differential. Before winding switching (cumulative mode), the machine is operated like a conventional three‐phase PMVM. The machine provides high torque density and high efficiency in this mode. After winding switching (differential mode), the back EMF and inductance of the machine are decreased significantly, which enable wide speed range operation and the attainment of high power factor in high‐speed operation.